2010
DOI: 10.1159/000265829
|View full text |Cite
|
Sign up to set email alerts
|

Benign Intraductal Papillary-Mucinous Neoplasm of the Pancreas Associated with Spontaneous Pancreaticogastric and Pancreaticoduodenal Fistulas

Abstract: Invasive intraductal papillary-mucinous neoplasms (IPMNs) of the pancreas may be associated with pancreaticogastric fistulas as shown by case reports. We report the case of a benign IPMN associated with pancreaticogastric and pancreaticoduodenal fistulas. A 70-year-old woman was admitted with intestinal obstruction. Computed tomography and MRI showed a large dilatation of the main pancreatic duct (>1 cm) with intraductal nodules, and pancreaticogastric and pancreaticoduodenal fistulas. Several features in imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…To our knowledge, there have been 8 published reports comprising 15 cases of IPMN with pancreatogastric fistulas (Table) (6-13). Koizumi et al (10) reported that the duodenum (24 cases, 59%), common bile duct (21 cases, 51%), and stomach (7 cases, 17%) were the organs most frequently affected by fistula formation. Kobayashi et al (6) observed fistula in other organs in 18 of 274 (6.6%) patients, 10 of whom had main-duct IPMN, 8 branch-duct IPMN, and 8 pancreatogastric formation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been 8 published reports comprising 15 cases of IPMN with pancreatogastric fistulas (Table) (6-13). Koizumi et al (10) reported that the duodenum (24 cases, 59%), common bile duct (21 cases, 51%), and stomach (7 cases, 17%) were the organs most frequently affected by fistula formation. Kobayashi et al (6) observed fistula in other organs in 18 of 274 (6.6%) patients, 10 of whom had main-duct IPMN, 8 branch-duct IPMN, and 8 pancreatogastric formation.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Spontaneous pancreaticoduodenal fistulas are not uncommon; depending on the study population, the incidence varies from 3% to 47%. 11 - 14 Duodenal and colonic fistulas occur more frequently compared to other sites due to their anatomic proximity. The majority of fistulas in the upper GI tract close spontaneously and can be managed conservatively compared to colonic fistulas, which require a higher rate of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A rarer cause of pancreatic fistula is intraductal pancreatic mucinous tumor (IPMT). Case reports of IPMT leading to fistula to the stomach, duodenum, bile duct, and colon have been reported [37][38][39]. Abundant secretion of mucus leading to pressure necrosis is thought to be the etiology of fistula formation in some of the patients [38].…”
Section: Pancreatic Fistulaementioning
confidence: 99%